FUZZY GRAVITATIONAL CLASSIFIER FOR CLASSIFYING IMBALANCED DATASETS - Sinciya, P.O; Celin, J. Jeya A (International Journal of Computer Sciences and Engineering, 2025)
Developing a precise and consistent model for classifying imbalanced medical data is one of the major challenges in machine learning and data mining. As the advanced growth in medical technology, a classy medical classification system is essential that make use of data mining algorithms to support medical diagnosis practice. Though the standard medical data seldom obeys the requirements of different knowledge engineering tools, most of the medical datasets are considered to be highly imbalanced with respect to their class label. So the imbalancing problem has been found to thwart the efficiency of the learning model. The only way to avoid this problem is to reduce the gap between both majority and minority class instances. In our approach a fuzzy gravitational classifier with weighting scheme is employed, in which weight is optimized using Particle swarm optimization algorithm. The technique is implemented and tested with three well known bench mark imbalanced dataset from UCI and KEEL repository. A comparative study is made with two existing classification methods viz. Weighted nearest neighbour and class based weighted nearest neighbour. Evaluation results shows our hybrid approach gives better performance on imbalanced data in terms of AUC, F-measure and G-mean